Navigating Digital Business Performance : A Bibliometric Exploration and Integrated Evaluation Framework - Adelia, Ajeng; Muhammad Haikal Rahman; Muhammad Wizdan Muthahari; Fasya Laras Pramisya; Lusiana Desy Ariswati; Muhammad Ramadhani Kesuma (Indo Publishing, 2025)
In order to capture the complex dynamics of platform ecosystems, digital transformation necessitates advanced performance measurements; nevertheless, Indonesia still relies on antiquated traditional measures that are unable to handle these complexity. In the fields of IT Governance, IT-Business Alignment, and IT Performance Measurement. Significant fragmentation is revealed by the analysis: new European clusters led by Loukis, Charalabidis, and Bernroider, which focus on e-government and SME applications, remain detached from a traditional Western cluster centered on Van Grembergen's work on COBIT and Balanced Scorecard. Chien-Chih Yu and other bridging figures provide a fragile connection between these groups. Additionally, citation trends show a move toward Asian-focused publications and open-access journals like Heliyon, which reflects increased regional relevance. In order to enable adaptive performance assessment, the research makes three contributions: (1) comprehensive mapping of bibliometric trends that provide insights into research dynamics; (2) an innovative evaluation framework that integrates quantitative and qualitative indicators, relevant to practitioners in developing countries such as Indonesia; and (3) policy recommendations to strengthen digital literacy in performance measurement. This paradigm promotes sustainable digital initiatives in developing economies, bridging theoretical underpinnings with practical implementations.